Learners’ Attitudes and Performance in Science Subjects in A-Level in Secondary Schools, in Mbarara, Uganda - AMIR, KABUNGA; Mohamed, Habiba C.; Mnjokava, Christina E. (IJRDO- Journal of Educational Research, 2016)
This research study aimed at investigating the learners’ attitudes and performance in science.The main objective of the study was to establish the relationship between learner’s attitudes andperformance in science subjects based on age and gender. Cross-sectional research design wasadopted for the study. Schools were randomly drawn from Mbarara district in Uganda. Thisgave a sample size of 300 form five and six secondary students. A questionnaire was used incollecting data for the study. The data was analyzed using SPSS to generate Pearson’s ChiSquare test, Spearman Rank Correlation and bivariate to test the hypotheses of the study. Thefindings of the study revealed that attitude, age and gender had significant relationship withstudents’ performance in science subjects. Therefore, students’ attitudes should be very centralto teachers, because affective dispositions are powerful predictors of students’ performance